Foucault, The Painter: Approach from the reading of Gilles Deleuze - Marcelo Zelaya Torres (HYBRIS: Revista de Filosofía, 2014)
This paper aims to chart a path through the reading Gilles Deleuze makes on the works of Michel Foucault, paying special attention to the articles that Deleuze writes, not only when the philosopher was alive but also post-mortem, and that make up the book published in 1986 entitled Foucault. This path will focus specifically on the descriptions that Foucault develops around Velasquez's Las Meninas in The Order of Things, which, according to Deleuze, "have the value of paintings". Paintings-descriptions, along with Magritte, Manet, prison, asylum, etc., constitute a light regime, a field of visibility, where his own philosophy shines. In this exercise we can follow not only Deleuze’s steps in his reading on Foucault, but also points of convergence between the two philosophers, despite having different philosophical projects